Golf putting under psychological pressure: Review of experimental studies of symptoms and prevention - Tanaka, Y. (Japan Journal of Physical Education, Health and Sport Sciences, 2014)
It is known that many athletes competing in various sports are likely to experience impaired motor performance under psychological pressure. Numerous studies have been conducted to clarify and overcome this problem, which impacts on various motor skills, and a variety of results have been reported. In this review, in order to exclude the influence of task-specific differences on interpretation of the results, experimental studies of the golf-putting task, which has been most widely used in previous studies of motor behavior under pressure, published between 1992 and 2013 were systematically reviewed by categorizing them into the following research paradigms: (1) Explanations of reduced performance under pressure in terms of attentional foci and attentional capacity, including the conscious processing hypothesis and distraction hypothesis. (2) Studies of psychological, physiological, and behavioral symptoms manifested under pressure, especially studies of cognitive and emotional processes in the psychological domain, arousal in the physiological domain, and performance outcome, kinematics, force control, and eye movement in the behavioral domain. (3) Studies investigating methods for preventing pressure-related performance loss, such as those involving quiet eye training for optimal eye movement, and manipulation of attentional focusing to prevent an increased internal focus of attention under pressure. It is suggested that the theoretical background developed in this review would be useful for gaining scientific knowledge about sports performance under psychological pressure from a wide range of perspectives on motor behavior.